Study of the Effect of the Driving Force on the Kinetics of CO2 Hydrate Growth in Coal Particles - Chuanhai, Liu; Ran, Chen; Baoyong, Zhang; Qiang, Wu; Qiang, Zhang; Qiong, WU (Frontiers in Energy Research, 2022)
Coal and gas outbursts are geological disasters occurring in the process of coal mining that can cause serious casualties and economic losses, among which CH4 is the main component of coal mine gas. However, there are still many coal seams around the world that are dominated by CO2. Although the frequency of CO2 gas outburst accidents is relatively low, CO2 outbursts are very violent, notably difficult to control and highly dangerous. The application of hydration curing technology to reduce the pressure and gradient of CO2 gas in the coal can effectively reduce the occurrence of coal and CO2 outburst. Accordingly, in this paper, experimental studies on the growth kinetics of CO2 hydrate with three driving forces (2, 2.5, 3 MPa) were carried out under four different coal particle sizes (C1: 0.425–0.850 mm, C2: 0.250–0.425 mm, C3: 0.180–0.250 mm, C4: 0–0.180 mm) to obtain kinetic parameters such as gas consumption, growth rate, and heat of decomposition during the synthesis of CO2 hydrate. The results show that the hydrate nucleation time in the same particle size system does not follow the same decreasing trend with increasing driving force. Gas consumption of CO2 hydrates in the same particle size system increased with increasing driving force, and there exists a critical value regarding the effect of the driving force on CO2 hydrate generation in coal particles with the particle size. Under the same temperature conditions, increasing the driving force in the particle size system could increase the CO2 hydrate growth rate. With decreasing coal particle size and increasing driving force, the promoting effect gradually exceed the inhibiting effect, which promote CO2 hydrate formation. Through linear fitting, an equation of the average growth rate of CO2 hydrates versus the driving force for the C1-C4 systems is fitted to provide a reference to predict the average CO2 hydrate growth rate. In the same medium, with increasing driving force, more heat is required for complete decomposition, which remains relatively stable, and the heat of decomposition of CO2 hydrates is the highest in the C1 medium, indicating that the presence of CO2 hydrates in the C1 system represents the most stable state.